PBX1: a TALE of two seasons—key roles during development and in cancer - Crisafulli, Laura; Brindisi, Matteo; Liturri, Mirko Giuseppe; Sobacchi, Cristina; Ficara, Francesca (Frontiers in Cell and Developmental Biology, 2024)
Pre-B cell leukemia factor 1 (PBX1) is a Three Aminoacid Loop Extension (TALE) homeodomain-containing transcription factor playing crucial roles in organ pattering during embryogenesis, through the formation of nuclear complexes with other TALE class and/or homeobox proteins to regulate target genes. Its contribution to the development of several organs has been elucidated mainly through the study of murine knockout models. A crucial role for human development has been recently highlighted through the discovery of different de novo pathogenic PBX1 variants in children affected by developmental defects. In the adult, PBX1 is expressed in selected tissues such as in the brain, in the gastro-intestinal and urinary systems, or in hematopoietic stem and progenitor cells, while in other organs is barely detectable. When involved in the t(1;19) chromosomal translocation it acts as an oncogene, since the resulting fusion protein drives pre-B cell leukemia, due to the induction of target genes not normally targeted by the native protein. Its aberrant expression has been associated to tumor development, progression, or therapy-resistance as in breast cancer, ovarian cancer or myeloproliferative neoplasm (MPN). On the other hand, in colorectal cancer PBX1 functions as a tumor suppressor, highlighting its context-dependent role. We here discuss differences and analogies of PBX1 roles during embryonic development and in cancer, focusing mainly on the most recent discoveries.